What Linguistic Conventions for Science Writing ? - SLOUGUI, Doudja (Journal of Human Sciences, 2009)
Research article writing is a critical issue for many non-English speaking scientists. If an article fails to meet the scientific community expectations, it is likely to get rejected. Recent research in applied linguistics and other fields has reported the existence of conventions that govern the research article genre. A considerable amount of studies has indicated that RA writing exhibits a conventional rhetorical patterning. Yet we do not know much about the linguistic conventions that govern the science article writing.  The purpose of this paper is to shed light on some of these features, as revealed by the revision work which two  papers -submitted for international publication- have undergone